Pemberian ASI Eksklusif dengan Kejadian Diare - Yampa Eksa Daidella Ghilari; Trisno Agung; Isabella Rahmawati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2018)
Background: Diarrhea is a disease with a high incidence in the world. One risk factor for diarrhea is that the motherdoes not give exclusive breastfeeding to her baby. The coverage of exclusive breastfeeding in Banguntapan IHealth Center Bantul from 302 infants as many as 197 (90%) infants who received exclusive breastfeeding.Objective: To determine the relationship and calculate the risk of exclusive breastfeeding with the incidence of diarrhea in Banguntapan I health center, Bantul.Method: This study is a type of quantitative research using methods analytical survey with crossectional approach.The population is mothers who have babies aged> 6-12 months in Banguntapan I Health Center, Bantul. The sampling technique used purposive sampling, with a total sample of 75 respondents.Results: From 75 samples there were 51 exclusively breastfed babies and 24 infants who were not given exclusivebreastfeeding. Babies with exclusive breastfeeding and having diarrhea as many as 3 babies (4.0%), while babieswith no breast milk exclusive and experienced diarrhea of 6 babies (8.0%). With the chi-square test obtained p valueof 0.026 (p> 0.05). The Prevalence Ratio value (RP) obtained a value of 4,250 (interval 90% trust).Conclusion: There is a relationship between exclusive breastfeeding and the incidence of diarrhea. Mothers whodo not give exclusive breastfeeding are 4,250 times more likely to be babies to experience diarrhea compared tomothers who give exclusive breastfeeding, and on a regular basis statistically significant (0.026).Keywords: Exclusive breastfeeding, incidence of diarrhea